2011
DOI: 10.1007/s00213-011-2394-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of two DRD2 gene polymorphisms with acute and tardive antipsychotic-induced movement disorders in young Caucasian patients

Abstract: Two associations were found between genetic variation TaqI_D and the -141C polymorphisms in the DRD2 gene and antipsychotic-induced MD; one with acute akathisia and one with tardive dyskinesia. These were previously reported to be associated with tardive dyskinesia and acute parkinsonism, respectively. These results suggest that the contribution of these DRD2 gene variants in the vulnerability of antipsychotic-induced MD takes place in a more general or pleiotropic way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 83 publications
(90 reference statements)
0
35
0
3
Order By: Relevance
“…The DRD2/ANKK1 marker rs1800497 (TaqIA) has yielded the most consistent findings, with two meta-analyses conducted prior to 2010 supporting an association with TD [136,137]. However, the two studies included in our review that reexamined this association yielded negative results [138,139]. Nevertheless, these studies hold little weight in view of the overall evidence, and the association between the TaqIA variant and TD susceptibility continues to be of clinical interest.…”
Section: Eps and Tdmentioning
confidence: 90%
“…The DRD2/ANKK1 marker rs1800497 (TaqIA) has yielded the most consistent findings, with two meta-analyses conducted prior to 2010 supporting an association with TD [136,137]. However, the two studies included in our review that reexamined this association yielded negative results [138,139]. Nevertheless, these studies hold little weight in view of the overall evidence, and the association between the TaqIA variant and TD susceptibility continues to be of clinical interest.…”
Section: Eps and Tdmentioning
confidence: 90%
“…Moreover, a number of investigations found the relationship between functional gene polymorphisms and antipsychotic-induced TD risk. These genes include the DRD2, DRD3, 5-HT 2A receptor, CYP450, GRIN2A, GSTM1, HSPG2, BDNF and SOD2 [6,[9][10][11]34,35]. However, the antipsychotic-induced adverse reaction (such as TD) in most cases probably does not depend on one single factor or on one single gene variant, but rather on many gene variants, gene-gene or gene-environment interactions [28].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have indicated some risk factors contributed to TD susceptibility, such as age, female gender, dosage and duration of antipsychotics [5]. Recent candidate gene association studies including genome wide association study (GWAS) have identified suscep-tibility genes for TD, such as dopamine D2 (DRD2), DRD3, 5-HT 2A receptor, GLI2, pyrophosphatase 2 (PPA2), heparan sulfate proteoglycan 2 (HSPG2), dipeptidyl peptidase-like protein (DPP)-6 and brainderived neurotrophic factor (BDNF) [6][7][8][9][10][11]. Additionally, several studies have suggested that the gene-gene interactions contributed to individual variations in TD.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, however, the prevalence of tardive dyskinesia (TD) is lower in Asian than western populations [28], suggesting that Asian MDD patients may have some advantageous for long-term treatment with AAs. These differences are thought to be from differences in the expression of genetic polymorphisms, such as the dopamine D3 receptor gene (DRD3) and DRD2 that are principally related to the development of movement disorders, although some debate still exists [29,30]. On the other hand, Asian patients were found to have greater susceptibility to developing anticholinergic side effects, blood dyscrasia and metabolic abnormalities, including hypertension, diabetes mellitus and weight gain, from antipsychotic treatment [5,31,32].…”
Section: Clinical Points For the Use Of Atypical Antipsychotics For Mmentioning
confidence: 99%